1993
DOI: 10.1007/bf02634373
|View full text |Cite
|
Sign up to set email alerts
|

In vitro stimulation of human endothelial cells by derivatized dextrans

Abstract: Derivatized dextrans exert a stimulatory effect on the in vitro growth of human umbilical vein endothelial cells (HUVEC). Measurements of growth were monitored by [3H]thymidine uptake and cell numbers. Our results show that some derivatized dextrans at 4 micrograms/ml (88 nM) increase the [3H]thymidine incorporation, whereas starting dextran (40,000 Da), dextran sulfate, and carboxymethyl dextran have no effect. In addition, heparin under similar experimental conditions shows a slight inhibitory effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…2 For the purpose of this study, dextran was chosen because this polysaccharide (a) stabilizes liposomes, 15,26 (b) increases the circulatory half-life of liposomes, 31 (c) reduces protein adsorption, 11 (d) is a good macromolecular drug carrier, 32,33 and (e) can be functionalized to endow various biologic properties. [17][18][19][20][21][22][23] Here, we compared the uptake by human endothelial cells of conventional liposomes and dextran-or functionalized dextrancoated liposomes using radioactive and fluorescent lipid probes. The polysaccharides were inserted during the liposome formation within the liposome membrane through a cholesterol moiety which acts as a hydrophobic anchor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 For the purpose of this study, dextran was chosen because this polysaccharide (a) stabilizes liposomes, 15,26 (b) increases the circulatory half-life of liposomes, 31 (c) reduces protein adsorption, 11 (d) is a good macromolecular drug carrier, 32,33 and (e) can be functionalized to endow various biologic properties. [17][18][19][20][21][22][23] Here, we compared the uptake by human endothelial cells of conventional liposomes and dextran-or functionalized dextrancoated liposomes using radioactive and fluorescent lipid probes. The polysaccharides were inserted during the liposome formation within the liposome membrane through a cholesterol moiety which acts as a hydrophobic anchor.…”
Section: Discussionmentioning
confidence: 99%
“…1) have been shown to exhibit heparin-like properties, such as anticoagulation capacities, 18 inhibition of smooth-muscle cell growth, 19 antiviral activities, 20,21 and anticomplementary activity in vitro and in vivo. 22 Functionalized dextrans (FDx) were also found to interact with human umbilical vein endothelial cells, 23 depending on the degree of substitution of specific chemical groups. In this study, the uptake by human endothelial cells of liposomes coated with dextran or FDx was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The effect on mitogenesis of HUVEC in the absence of serum leads t o the conclusion that exogenous growth factors are not involved in the proliferative capacity of these materials (ref. 11 1. It appears that benzylamide sulfonate groups play an important role in the stimulation of HUVEC.…”
Section: B L O a C T L V E P O L Y M E R S And Cellsmentioning
confidence: 99%
“…[11][12][13] At the cellular level, we have demonstrated that CMDBS was able to mimic heparin and regulate proliferation of different types of cells. [14][15][16] Independently of cell proliferation regulation, we have shown that CMDBS could significantly modulate the expression of collagen biosynthesis in vascular cells. 17,18 General laws seem to sustain wound healing or tissue repair, whatever the nature and location of the injured tissue.…”
Section: Introductionmentioning
confidence: 99%